2019
DOI: 10.1097/md.0000000000016445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on the levels of BDNF and executive function in adolescents

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…However, the association of the Val66 Met genotype with BDNF serum or plasma levels in children, adolescents or adults, was not confirmed in other studies [ 12 , 25 , 26 ]. Peripheral level of BDNF depends on numerous factors such as age, gender, hormonal status, circadian variation, platelet count, diet and exercise [ 12 , 27 , 28 ]. This complex mechanism of regulation of BDNF levels could be the reason for the contradictory results regarding the association of the Val66Met polymorphism with peripheral BDNF levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of the Val66 Met genotype with BDNF serum or plasma levels in children, adolescents or adults, was not confirmed in other studies [ 12 , 25 , 26 ]. Peripheral level of BDNF depends on numerous factors such as age, gender, hormonal status, circadian variation, platelet count, diet and exercise [ 12 , 27 , 28 ]. This complex mechanism of regulation of BDNF levels could be the reason for the contradictory results regarding the association of the Val66Met polymorphism with peripheral BDNF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, BDNF might be a key mediator of the effects of exercise on structural brain markers of depression. An accumulating number of studies have demonstrated that exercise training results in significant upregulation of BDNF and elevation of neurogenesis in human and animal models (de Azevedo et al., 2019; Liu & Nusslock, 2018; Pereira et al., 2013; Sleiman et al., 2016; Wrann et al., 2013). There are also some clinical trials evaluating anti‐depressive effects of exercise training in patients with breast cancer and its impact on the serum levels of BDNF (Witlox et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is much heterogeneity in study designs with exercise training, as has been noted in other systematic review protocols. [32,33]…”
Section: Discussionmentioning
confidence: 99%